Prophylactic Decompression for Cervical Stenosis in Jeune Syndrome: Report From a Single Institution. Issue 13 (1st July 2020) - Flanders, Tracy M.; Franco, Alier J.; Lott, Carina; Anari, Jason B.; Cahill, Patrick J.; Storm, Phillip B.; Heuer, Gregory G.
Abstract : Study Design: This is a level IV retrospective descriptive study at a single institution. Objective: The objective of the study was to determine the preoperative signs or symptoms prompting cervicomedullary imaging in Jeune syndrome. Summary of Background Data: Jeune syndrome is a rare autosomal recessive disorder that results in pulmonary compromise from abnormal development of the thorax. Multiple medical comorbidities complicate timely diagnosis of cervicomedullary stenosis, which neurologically jeopardizes this patient population with regards to improper cervical manipulation. Currently, explicit screening of the cervicomedullary junction is not advocated in national guidelines. Methods: The User Reporting Workbench and Center for Thoracic Insufficiency Syndrome (CTIS) Safety Registry was queried for patients with Jeune syndrome under the age of 18 with cervicomedullary stenosis with or without suboccipital craniectomy/craniotomy evaluated at the authors' institution from January 1, 2007 to August 21, 2018. The primary outcome was the clinical reason for cervicomedullary screening. Secondary outcomes were: age at time of surgery, preoperative myelopathy (spasticity, urinary retention), hydrocephalus, postoperative deficits (respiratory, motor, swallowing difficulty), and need for cervical fusion. Results: Of 32 patients with Jeune syndrome, four (12.5%) had cervicomedullary stenosis requiring decompression. The average age at surgery was 5.25 months (2–9 mo). Two patients underwent imaging due to desaturation events while the other two patients were diagnosed with cervical stenosis as an incidental finding. No patients exhibited clinical myelopathy. Two patients had baseline preoperative swallowing difficulties. None of the patients postoperatively required cervical fusions, nor did they exhibit respiratory deficits, motor deficits, or worsening swallowing difficulties. Conclusion: Jeune patients should be routinely screened for cervicomedullary stenosis and undergo subsequent prophylactic decompression to minimize or eliminate the development of irreversible neurologic compromise. Level of Evidence: 4 Abstract : Jeune patients are complex with multiple medical comorbidities that can cloud a timely diagnosis of cervicomedullary stenosis. These patients often require several surgical procedures, and hyperextension injury can result in irreversible neurologic compromise. Spinal surgeons must be vigilant in screening for cervical stenosis and offer prophylactic decompression in this population.